(untitled) (Bangladesh Journal of Pharmacology, 2014)
Antibiotic resistance is a major challenge to combat tuberculosis. Several reports of antibiotic resistance strains of Mycobacterium tuberculosis is strongly demanding the need of new and alternative antibiotics for its inhibition. Therefore, current investigation is an attempt to screen few lead molecules for the inhibition of arbinosyl transferase enzyme of M. tuberculosis. The inhibition of this enzyme is an established target of many antibiotics especially ethambutol. Herein, we have considered the structure of ethambutol as a starting point to screen active compound then ethambutol. Similar compounds were searched in chemical database and six compounds were identified and considered as selective arbinosyl transferase inhibitor based on physiochemical properties, bioactivity and ADME with least docking score. The compounds viz. ZINC00388344, ZINC003884, Chemspider2057082, ZINC-00388344, ZINC0038846, Chemspider2057082, Etha17 (analog) and Etha10 (analog) were finally screened and recommended for in vitro investigation.